Flipped-learning and physical-expressive games to promote healthy eating habits in college students. - Cristina Castejón-Riber; Manuel Sánchez-Ostos; Rocío Medrano Ureña; Pamela A. Koch (Journal of Sport and Health Research, 2026)
This study aimed to evaluate the effectiveness of a Food and Nutrition Education (FNE) intervention using flipped-learning and physical-expressive games compared to synchronous and asynchronous online lectures in promoting healthy eating habits among college students studying to become physical education teachers. University students often adopt unhealthy dietary habits. Innovative FNE methods, such as flipped-learning (FL) and physical-expressive games, may enhance motivation and behavioral change through active and engaging learning environments. A quasi-experimental, non-randomized design was applied with 139 Spanish college students divided into three groups: synchronous online lectures (SOL), flipped-learning and games (FL&G), and asynchronous control (C). Each group received nutrition content differently. Dietary intake was assessed pre- and post-intervention using a validated food frequency questionnaire. Non-parametric tests and Quade's ANCOVA were used for analysis. All interventions increased vegetable intake significantly, been FL&Gintervention significantly more effective than SOL (p=0,001) and C(p=0,000). Improvements in nut intake were also significant for FL&G and SOL groups. No intervention significantly improved fruit intake or reduced unhealthy food consumption overall, though burger intake was significantly lower in the FL&G group compared to SOL. FL&G was more effective for vegetable intake and encouraged physical activity during learning, suggesting its potential as a appropriate FNE strategy. However, its impact on other dietary behaviours was limited. Combining flipped-learning with physical-expressive games shows promise for improving healthy eating, particularly vegetable intake, in college students. Broader and longer interventions are recommended to strengthen outcomes.